Protective effects of diallyl disulfide on carbon tetrachloride‐induced hepatotoxicity through activation of Nrf2. Issue 5 (1st December 2013) - Lee, In‐Chul; Kim, Sung‐Hwan; Baek, Hyung‐Seon; Moon, Changjong; Kim, Sung‐Ho; Kim, Yun‐Bae; Yun, Won‐Kee; Kim, Hyoung‐Chin; Kim, Jong‐Choon
ABSTRACT: This study was conducted to investigate the potential effects of diallyl disulfide (DADS) on carbon tetrachloride (CCl4 )‐induced acute hepatotoxicity and to determine the molecular mechanisms of protection offered by DADS in rats. DADS was administered orally at 50 and 100 mg/kg/day once daily for 5 consecutive days prior to CCl4 administration. The single oral dose of CCl4 (2 mL/kg) caused a significant elevation in serum aspartate and alanine aminotransferase activities, which decreased upon pretreatment with DADS. Histopathological examinations showed extensive liver injury, characterized by extensive hepatocellular degeneration/necrosis, fatty changes, inflammatory cell infiltration, and congestion, which were reversed following pretreatment with DADS. The effects of DADS on cytochrome P450 2E1 (CYP2E1), the major isozyme involved in CCl4 bioactivation, were also investigated. DADS pretreatment resulted in a significant decrease in CYP2E1 protein levels in dose‐dependent manner. In addition, CCl4 caused a decrease in protein level of cytoplasmic nuclear factor E2‐related factor 2 (Nrf2) and suppression of nuclear translocation of Nrf2 concurrent with downregulation of detoxifying phase II enzymes and a decrease in antioxidant enzyme activities. In contrast, DADS prevented the depletion of cytoplasmic Nrf2 and enhanced nuclear translocation of Nrf2, which, in turn, upregulated antioxidant and/or phase II enzymes. These results indicate that the protective effects of DADS against CCl4 ‐induced hepatotoxicity possibly involve mechanisms related to its ability to induce antioxidant or detoxifying enzymes by activating Nrf2 and block metabolic activation of CCl4 by suppressing CYP2E1. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 538–548, 2015.